Handbook of contemporary Japanese religions - Prohl, Inken; Nelson, John K. (Brill handbooks on contemporary religion 1874-6691, 2012)
"Representing work by some of the leading scholars in the field, this volume presents important topics in the religious environment of contemporary Japan by surveying exciting trends, religious change and innovation, and the interactivity of religion with market and global forces"--Provided by publisher